They don't get me I'm part of the union: Trade unions in the German parliament - Michael Berlemann; Klaus W. Zimmermann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
This article focuses on the role of unionized members in parliament. Unions have not been successful in increasing their monopoly power during the last decades in the US. Similarly, a recent study for Germany comes to the result that union members in the Bundestag cannot be seen as the parliamentary arm of the trade unions. However, we present contradicting empirical results by showing that the degree of unionization of parliamentary members has a negative impact on economic growth and increases inflation while unemployment remains unaffected. Thus, at least German trade unions do not seem to be as weak at the parliamentary stage as they often claim to be.
Keywords: J51; 330; trade unions; unemployment; growth; inflation